Computer Application Technology and Practice in the Big Data Environment - Ma, Shenwen (Journal of Artificial Intelligence and Information, 2025)
In recent years, China has undergone numerous reforms and innovations in the field of technology, successfully entering the era of big data. In this era, there has been significant progress in computer application technology. Within the context of the big data era, computer application technology faces numerous challenges, but it also presents boundless opportunities. Continuous reform, innovation, and breakthroughs are essential to construct application thinking, approaches, and patterns that align with the characteristics of big data. Therefore, its imperative that we fully understand and comprehend big data and actively embrace the impact it brings. This paper delves into a thorough exploration of various types of computer application technologies within the big data environment, as well as future development trends and practical implementations. Furthermore, it provides corresponding recommendations with the aim of offering valuable insights for related endeavors.